Tren Gaya Hidup Sehat dan Saluran Komunikasi Pelaku Pola Makan Food Combining - Sufa, Siska Armawati; Christantyawati, Nevrettia; Jusnita, Raden Ayu Erni (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
This research is concerned with the dissemination of information about healthy lifestyle trends that have been popular in Indonesia through Food Combining as a process of diffusion of innovation in health communication. By applying the diet Food Combining is expected that the human body will grow healthier, full of energy, and free from disease. Problems to be studied are about: 1) What motivates the perpetrators of diet combining diet in applying a healthy lifestyle? and 2) What channels of communication are used to find information related to diet combining? as well as 3) How to interact with the community of other food combining actors across Indonesia?This research uses qualitative methodology, with the object of research is various media information (print media, social media, and electronic media) along with all communication channel used by food combiner (member or community) Food Combining Indonesia with approach of Innovation Diffusion Theory.The results concluded that food combining is a new trend of healthy lifestyle of today that is motivated physiological needs which is the hierarchy of the most basic human needs to survive, including keeping the body fit and healthy and free from all kinds of diseases. While the communication channels in the process of diffusion of innovation in order to disseminate information and knowledge about healthy food lifestyle trends is done through social media with two-stage communication method which is a combination between the use of mass media channels and interpersonal channels by interacting through: personal contact, chatting applications, social media group, and gathering. Keywords: communication channels, innovation diffusion, health communication, healthy lifestyle, food combining